Dari Moralitas Normatif menuju Emansipasi Sosial: Rekonstruksi Amar Ma‘ruf Nahi Munkar dalam Teologi Konseling Profetik - Muhammad Robbi Sudrajat; Resky Adella; Amita Fiqi; Ali Hasan (Indo Publishing, 2026)
This article departs from the epistemological crisis in contemporary Islamic studies, which reveals a disconnection between religious texts and the social realities of modern society. The concept of amar ma‘ruf nahi munkar has generally been understood in normative, legalistic, and moralistic terms, functioning more as an instrument of social control than as a mechanism for humanistic and emancipatory social transformation. On the other hand, developments in critical social sciences and modern counseling approaches have not yet been adequately integrated into the paradigm of Islamic theology. The research gap lies in the limited studies that reconstruct amar ma‘ruf nahi munkar as a form of social counseling grounded in a theology of advocacy through a prophetic-emancipatory approach. This article employs the theoretical frameworks of prophetic theology, social hermeneutics, and emancipatory counseling theory to construct a new paradigm for the relationship between text and context in Islamic studies. This research is a qualitative library study using a critical hermeneutic approach and theological-social discourse analysis of primary and secondary sources in Islamic studies, philosophy, and social sciences. The article argues that amar ma‘ruf nahi munkar needs to be reconstructed from a paradigm of moral judgment into a paradigm of social assistance that is dialogical, participatory, and transformative. Through a prophetic-emancipatory counseling approach, religion functions not merely as a source of normative legitimacy, but also as a praxis of social liberation that restores human dignity.